Assessment of patients' self-reported levels of adherence to postoperative restrictions following total hip replacement. (December 2022) - Theaker, Justine; Oldham, Jackie; Callaghan, Michael; Parkes, Matthew
Abstract: Background: Postoperative precautions that limit hip movement reduce the incidence of postoperative dislocation following total hip replacement (THR). It is assumed that patients adhere to these precautions, but true adherence is unknown. Aims: To assess adherence to postoperative precautions, including bending, twisting, crossing of legs, sleeping position and sitting position following primary THR surgery. Methods: A self-reporting questionnaire explored patient adherence to precautions following primary THR. Questionnaires were sent to 120 patients following elective primary THR at two orthopaedic centres in England between November 2016 and April 2017. Patients were also asked to report the duration of adherence and the difficulty associated with adherence to each of the precautions. Results: Eighty-three percent (99/120) of patients responded. Of these, 56% (56/99) were female and 44% (44/99) were male. Mean age was 66.0 (standard deviation 9.4) years. Seventy-six percent of patients were classified as 'highly adherent' to the precautions in hospital, and this reduced to 68% when patients went home. The median duration of adherence to the precaution to avoid crossing legs was 6 weeks [interquartile range (IQR) 6–6]. For the remaining four precautions, the median duration of adherence was consistently 6 weeks (IQR 4–6). Conclusion: High levels of adherence to precautions following THR were identified. However, patients reported difficulty adhering to the precautions, which may explain why 24% of patients were not able to adhere to the precautions> 90% of the time. Patients reported that the most difficult precaution to adhere to was supine sleeping, and the least difficult precautions to adhere to were avoiding crossing legs and using a raised chair.